If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -3 = 7 Reorder the terms: -3 + 5t = 7 Solving -3 + 5t = 7 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5t = 7 + 3 Combine like terms: -3 + 3 = 0 0 + 5t = 7 + 3 5t = 7 + 3 Combine like terms: 7 + 3 = 10 5t = 10 Divide each side by '5'. t = 2 Simplifying t = 2
| X/18+1=-3 | | (a^8b^2)(a^6b^8)= | | 4x-6x=x-9 | | b=85+(10+7)w | | 10x/5x-1=5+2/5x-1 | | 7x-(-4)=54 | | 7(r-1)-3=2r+5 | | -7(n+7)=4n-16 | | 4x+9-x= | | ln(4-2x)+ln(9-3x)=21n(x+1) | | 2(9x+5)=-26 | | 3z+1/4=4z+7/4 | | 86=-70+13x | | 2b+4028=51514 | | 17+-5= | | -2(4x+2)=12 | | 5x-x+2=2x+2x+2 | | 2(2x+30)+4x=360 | | (2-4i)+(1-4i)= | | 0=x^2-1 | | 11b-2b= | | 13+(-6n)+(-15)+(-5n)= | | 1.1x+-5.4=-10 | | 5/9x=5/3 | | 1/5x+2/5x+3=18 | | (5-8*2)+12=-54 | | 11-2(3m-10)=6(4-m) | | x/-3+2=7 | | 10x=25x-3 | | 2x+3(x+7)=-29 | | -5=m-6+6 | | (12x+16)=10-3(x-2) |